Simulation-Based Examination of Arterial Line Insertion Method Reveals Interdisciplinary Practice Differences. Issue 2 (April 2020) - Golden, Antoinette; Alaska, Yasser; Levinson, Andrew T.; Davignon, Kristopher R.; Lueckel, Stephanie N.; Lynch, Kenneth A.; Jay, Gregory; Kobayashi, Leo
Abstract : Introduction: Arterial cannulation is frequently performed on intensive care unit (ICU) and operating room patients; a 1% complication rate has been reported. Investigators applied simulation to study clinical providers' arterial catheter (AC) insertion performance and to assess for interdisciplinary and intradisciplinary variation that may contribute to complications. Methods: Anesthesia, medical critical care, and surgical critical care providers with AC insertion experience were enrolled at 2 academic hospitals. Each subject completed a simulated AC insertion on an in situ task trainer. Using a Delphi-derived checklist that incorporated published recommendations, expert opinion, and institutional requirements, 2 investigators completed offline video reviews to compare subjects' technical performance. Results: Ten anesthesia, 11 medical ICU (MICU, 1 excluded), and 10 surgical ICU (SICU) subjects with significant between-group differences in training level and AC insertion experience were enrolled for 2 years. Differences in procedural planning, equipment preparation, and patient preparation steps did not attain significance across groups except for anesthesia participants using only ad hoc AC kits, and MICU and SICU subjects preferentially using commercial kits ( P < 0.001). Time-outs were completed by 1 anesthesia subject, 5 MICU subjects, and 4 SICU subjects ( P = 0.29, NS). For proceduralist preparation steps, fewer anesthesiology subjects donned gowns ( P < 0.001). Only MICU subjects used ultrasound guidance ( P = 0.0053), and only MICU (100%) and SICU (100%) subjects sutured ACs in place. Overall observance of sterile technique was similar across groups at 70% to 100% ( P = 0.32). Conclusions: Simulated AC insertions revealed procedural performance variability that may derive from individual provider differences, discipline-based practice parameters, and setting-specific cultural factors. Abstract : Supplemental digital content is available in the text.